Reducing school violence: Considering school characteristics and the impacts of law enforcement, school security, and environmental factors. Issue 3 (15th August 2016) - Crawford, Charles; Burns, Ronald
Abstract : Purpose: Recent highly publicized acts of violence and shootings on school campuses have prompted numerous crime prevention responses. The purpose of this paper is to assess the impact of protective measures such as law enforcement, security policies, and school/neighborhood characteristics on school violence within the context of the racial composition of the school and grade level. Design/methodology/approach: The data used in this study were part of the School Survey on Crime and Safety collected in 2006. The dependent measures of school violence include reports of serious violence, physical attacks/fights, gun or knife possession, and threats and attacks with a weapon. The sample was divided by racial composition of the school (predominately white, and predominately minority schools) and by grade level (high schools, and all other grades). A negative binomial regression was conducted due the count-based dependent variables. Findings: Findings revealed that minority schools often face higher levels of reported violence and had a heavier law enforcement presence, which often had mixed or counterproductive results for reducing school violence. School characteristics, such as reports of bullying, location, gang activity, and security measures yielded numerous statistically significant results. Research limitations/implications: Officials proposing school violence prevention efforts should strongly consider the importance of school and community characteristics, most notably grade level, and the unique context of a predominately white or minority school as there were different statistically significant results. Furthermore, officials should be cautious about relying on simple efforts such as more security personnel to address school violence. Violence and crime on school grounds should not be viewed as being isolated from violence and other forms of crime in the community. Policy recommendations and suggestions for future research are provided. Originality/value: This study differs from much of the previous literature, which typically examines student and administrator attitudes about victimization and crime prevention. The current study examines detailed information on the effects of school violence prevention efforts and moves beyond most other works as it considers school safety approaches within the context of racial composition of the school and by different grade levels.